Level of Physical Activity and Mass Body Index of Students in the Pandemic Period - Adi S; Mohamad Da’i; Olivia Dwi Cahyani (STKIP Muhammadiyah Kuningan, 2021)
Physical activity is essential in maintaining health. This study aimed to investigate the level of physical activity of students at the time of the COVID-19 pandemic. The International Physical Activity Questionnaire (IPAQ) questionnaire was used to examine students' level of physical activity. Students who participated in this study were 1367. The number of female students in this study was 920, while male students were 447. The results showed there were differences in physical activity between male and female students. The average activity value of male students is three medium categories, while female students are two low categories. The biological activity of male students is one level higher than female students. The female student body mass index is included in the